Metabolic versatility and nitrate reduction pathways of a new thermophilic bacterium of the Deferrivibrionaceae: Deferrivibrio metallireducens sp. nov isolated from hot sediments of Vulcano Island, Italy - Grégoire Galès; Mélanie Hennart; Maverick Hannoun; Anne Postec; Gaël Erauso (PLoS ONE, 2025)
A novel thermophilic (optimum growth temperature ~ 60 °C) anaerobic Gram-negative bacterium, designated strain V6Fe1T, was isolated from sediments heated by the hydrothermal circulation of the Aeolian Islands (Vulcano, Italy) on the seafloor. Strain V6Fe1T belongs to the recently described family Deferrivibrionaceae in the phylum Deferribacterota. It grows chemoorganotrophically by fermentation of proteinaceous substrates and organic acids or by respiration of organic compounds using fumarate, nitrate, Fe(III), S°, and Mn(IV) as electron acceptors. The strain V6Fe1T can also grow chemolithoautotrophically using H2 as an electron donor and nitrate, nitrous oxide, Fe(III), Mn(IV), or sulfur as an electron acceptor. Stable isotope probing showed that V6Fe1T performs denitrification with nitrate reduction to dinitrogen and Dissimilatory Nitrate Reduction to Ammonium (DNRA). Culture experiments with RT-qPCR analysis of target genes revealed that strain V6Fe1T performs DNRA with the nitrite reductase formate-dependent NrfA and denitrification with an Hcp protein and other redox partners yet to be identified. Genomic analysis and experimental data suggest that strain V6Fe1T performs autotrophic carbon fixation via the recently discovered reversed oxidative TCA cycle (roTCA cycle). Based on genomic (ANI) and phenotypic properties, strain V6Fe1T ( = DSM 27501T =  JCM 39088T) is proposed to be the type strain of a novel species named Deferrivibrio metallireducens.